Analising Students’ Perceptions in the Learning of English Vocabulary through Islamic Scripture Entitled ‘Al-Ghazali on Islamic Guidance’ or Bidayatul Hidayah - Nur Dalila Mohamad Nazri; Adibah Sulaiman; Anita Ismail (Universiti Sains Islam Malaysia, 2024)
The objectives of this paper is two fold. Firstly, it aims at finding students’ perceptions on the learning of English vocabulary in Al-Ghazali on Islamic Guidance or Bidayatul Hidayah, which is a great scripture of Islam written by Al-Imam Muhammad Bin Muhammad Bin Muhammad Bin Ahmad Alghazali Attusi or also known as Imam Al-Ghazali R.A. Secondly, it is to obtain students’ perceptions on the problems that occurred thoroughout the teaching and learning activities and how to improve them. This qualitative research adopts two techniques – observation and interview. It is discovered that majority of students show great interest to learn English through this scripture and their knowledge on English vocabulary has generally improved. The researcher also identifies the problems and lists the possible recommendations for improvement of such activity in the future. It is hoped that this study can shed some lights on how to better integrate Islamic elements in the teaching and learning of English language, as well as to produce active, autonomous and lifelong students; who as well, appreciate the ancient scriptures of Islam.